UKRAINIAN ENCYCLOPEDIAS AND DICTIONARIES IN VIEW OF SPREADING GEOLOGICAL KNOWLEDGE - ZHELEZNIAK, Mykola; ISHCHENKO, Oleksandr; BORTNYK, Sergii (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Encyclopedic literature and dictionaries devoted to geological sciences were overviewed in the article. The authors emphasize the lack of basic Ukrainian geological encyclopedia and provide arguments for the necessity of its appearance. They substantiate the importance of dictionaries representing specific subject lexicon, in particular geological terminology: "Dictionary of Geological Terminology" (1923), "Russian-Ukrainian Geological Dictionary" (1959), "Russian-Ukrainian Dictionary of Geological Terms" (1993), "Russian-Ukrainian Geological dictionary" (2011), "Ukrainian-French-English Dictionary of Geology, Geophysics, Well Drilling, and Oil, & Gas industry" (2011), "Russian-Ukrainian Geological Dictionary" (2016), "Geological Dictionary: Open Educational and Scientific Web Resource" (2017), "Russian-Ukrainian Geological Dictionary" (2018), "Ukrainian-Russian-English Dictionary of Geological Terms" (2020), and other mineralogical, geodetic, mining, petrographic dictionaries. The results show that Ukrainian encyclopedic and lexicographic literature does not provide knowledge of all geological sciences despite a fairly large number of encyclopedias and dictionaries (in total, over 40 sources were found), as there are dictionaries and encyclopedias encompassing only some particular geological fields. The authors also reflect on the issue of the distribution of subject encyclopedias and dictionaries in educational sphere today, when Wikipedia is considered to be the most popular online reference work in the world. The authors conclude that it is necessary to build a modern geological encyclopedia as a unified Ukrainian language source of reliable reference knowledge on geology.